Development of monovalent recombinant vaccine against streptococcus infection in hybrid red tilapia (Oreochromis spp.) - Rahmatullah, Muhammad (2018)
Tilapia (Oreochromis niloticus) is one of the most cultured species in the world. However, bacterial disease caused by Streptococcus spp. is one of the major problems affecting farmed tilapia worldwide. Hybrid red tilapia is highly susceptible to this disease and mortality may reach up to 70% within a week. Thus, the study was conducted to develop a recombinant vaccine of S. agalactiae, Millud II and S. iniae, TSK_2 previously isolated from infected tilapia. The isolates were successfully characterised as S. agalactiae and S. iniae respectively by species-specific PCR assay. The result confirms the amplification of 300 bp amplicons of 16S rRNA gene and sequence analysis demonstrated 98% similarity with complete genome of S. iniae, TSK_2 in BLASTn study. In addition, PCR amplification with primers specific for S. agalactiae 16S rRNA confirmed the target amplicons of 220 bp from positive control of bacterial DNA for S. agalactiae, Millud II.